2016
DOI: 10.1590/0037-8682-0241-2016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antischistosomal activity of venom from the Egyptian snake Cerastes cerastes

Abstract: Introduction:We studied the potential in vitro antischistosomal activity of Cerastes cerastes venom on adult Schistosoma mansoni worms. Methods: Live specimens of the horned viper snake, C. cerastes were collected from the Aswan Governorate (Egypt). Venom was collected from snakes by manual milking. Worms of S. mansoni were obtained from infected hamsters by perfusion and isolated from blood using phosphate buffer. Mortality rates of worms were monitored after 3 days of exposure to snake venom at LC 50 and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Thus they can be potentially used for drug discovery (Rivero et al 2011;Vigerelli et al 2014;Neto et al 2015). Hassan et al (2016) studied the potential antischistosomal activity of the Egyptian snake, Cerastes cerastes venom, in vitro. They found that it causes mild to severe tegumental damage to Schistosoma worms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus they can be potentially used for drug discovery (Rivero et al 2011;Vigerelli et al 2014;Neto et al 2015). Hassan et al (2016) studied the potential antischistosomal activity of the Egyptian snake, Cerastes cerastes venom, in vitro. They found that it causes mild to severe tegumental damage to Schistosoma worms.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only very few other studies addressed animal-derived compounds and their antischistosomal activities. These are compounds from sea cucumbers, skin secretions of a South-American tree-frog species, and undefined compounds from snake venom [3, 7072]. From insects, so far only two complex product mixtures, but no defined compounds, were described to have direct or indirect anthelminthic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis is one of the most predominant parasitic infection diseases worldwide. The results in Table 1 exhibited that the essential oil of A. cepa bulbs showed high antischistosomal activity (25 % -75 %) and shrinking rate (50% -70%) at concentration 500µg/mL at time interval 1hr to 24 hrs (Hassan et al, 2016). Also, BuOH fraction derived from MeOH extract showed more potent antischistosomal activity (25 % -50 %) and the highest shrinking rate (25 % -75 %) at concentration 500 µg/mL at time interval 1hr to 24hrs.…”
Section: In Vitro Antischistosomal Activitymentioning
confidence: 99%